Health status among NEET adolescents and young adults in the United States, 2016-2018 - Raeven Faye Chandler; Alexis R. Santos Lozada (Elsevier, 2021)
Adolescents and young adults not employed or in education/training (NEET) could be at higher risk of adverse health outcomes. Approximately 4.6 million Americans aged between 16 and 24 fall in this group. However, differences in health between NEET and non-NEET population remain unaddressed. This study examines the association of NEET status and poor/fair self-reported health status (SRH), among adolescents and young adults in the United States. Data for this study come from the 2016-2018 National Survey on Drug Use and Health (NSDUH). Our analytical sample consisted of 53,690 respondents. We used logistic regression models to investigate the association between NEET and health status in the United States, while controlling for potential covariates. Approximately 14% of our analytical sample was classified as NEET. NEET report poor/fair health status at higher rates than their counterparts who remained in school and/or had a job (11.30% vs. 5.62%). The NEET population was older, had a higher proportion of non-Hispanic Blacks, engaged in more smoking but in less alcohol drinking than non-NEET. In our initial model, NEET were more likely report poor/fair SRH than their non-NEET counterparts (OR = 2.14; p < 0.001). This difference remains strong when demographic and socioeconomic characteristics are accounted for in our empirical models (OR = 1.93, p < 0.001). In our fully specified model, which accounts for health behaviors, NEET continue to have higher odds of reporting poor/fair SRH (OR = 1.77, p < 0.001). Our analyses suggest that NEET populations report worse health than non-NEETs. The health of this population may improve if interventions to reinsert them into either education or employment are effectively deployed.